STUDI ADAPTASI PETANI DALAM PERTANIAN PADI SAWAH MENGHADAPI PERUBAHAN IKLIM Dl NAGARI SURIAN KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - Linda, Oktavia Roza (STKIP PGRI Sumbar, 2014)
ABSTRACTThis study aimed Â is to determine the Adaptation of Rice Farmers in Agricultural faceof climate change in Nagari Surian Sub Solok Regency Pantai Cermin as seen from : 1 ) Knowledge of paddy rice farmers , 2 ) Experience lowland rice farmers , 3 ) The behavior of lowland rice farmers . This research is descriptive . The population in this study is the lowland rice farmers in Nagari Surian Mirror Coastal District of Solok district that is numbered 927 people . The sample of respondents was taken with the proportional random sampling technique to sample totaled 57 lowland rice farmers . Data analysis techniques using analysis with the percentage formula and a Likert scale . The technique of collecting data through questionnaires instruments. The results of the study found that : Knowledge of lowland rice farmers on the climate change phenomenon in Nagari Surian Sub-District Pantai Cermin of Solok district , said farmers are generally not aware of ( 78.95 % ) , with 62.3 Likert scale that are strong in the criteria . Lowland rice farmers farming experience is in Nagari Surian District of Solok Regency Mirror Beach , generally say 15 years ( 47.37%), with 57.8 Likert scale that are at sufficient criteria. Behavior management of lowland rice farmers in terms of the use of organic fertilizers An , generally farmers say always use organic fertilizers An ( 68.42 % ) , with 53.65 Likert scale that are at sufficient criteria.Â Â